An Empirical Study on Investor Awareness and the Impact of Cryptocurrency - Mythili, D.; Ganeshwari, M.; Mohammad, Suleiman Ibrahim; Anitha, B. Merceline; Divya, D.; Vasudevan, Asokan (International Review of Management and Marketing, 2025)
Crypto-tech is a technology secured by cryptography, which enables the exchange of data and facilitates duplicated and distributed transactions across the entire network of computer systems on the blockchain. This paper aims to study cryptocurrency’s Awareness, perception, and impact among investors with special reference to Coimbatore city. This study will help provide baseline information on the factors influencing investors in cryptocurrency investing. The study found that cryptocurrency is likely to become the next financial platform due to the large amount of cryptocurrency flows in different systems, the huge increase and growth in cryptocurrency consumption and production, and the opportunities that cryptocurrency systems offer. And the level of awareness and preference in the use of cryptocurrency is moderate. However, investors are not yet fully aware of the dangers of using cryptocurrencies. Many cryptocurrency forms do not yet qualify for that level of trust. Investors should take extra precautionary measures when using cryptocurrency until it is well maintained. The future of the cryptocurrency concept is bright as there are many opportunities for positive change and progress in the e-business and e-payment sectors. As technology advances rapidly, cryptocurrency development continues.